The impact of using an integrated accounting information system on the quality of accounting information - Fouad Abdul Mohsen Al - Jubouri (Iraqi Journal for Administrative Sciences, 2025)
This research aims at examining sample of opinions of the supervisors of Al- Noora Factory, one of the factories of the Ministry of Iraqi Industry. Concerning the impact of the Accounting Information System in providing accounting information having the high quality and assisting the directorate in rational decision in obtaining super profits through reviewing Accounting Information System in the factory and manifesting types of accounting information which is produced by this system. The research has concluded to several important recommendations in promoting the usage of the Accounting Information System in a method that could proceed accounting information having high quality and being effective to take a decision.